Day 1 Mon, August 31, 2020 2020
DOI: 10.2118/200315-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Amphoteric Surfactant for CO2 Foam Applications: A Comparative Study

Abstract: In a surfactant-alternating-gas (SAG) injection, stable foams form viscous barriers and divert fluids, thereby providing conformance for enhanced oil recovery (EOR). Once foam decays, injected gas resumes preferential flow through thief zones, demonstrating the need for higher foam stability. Thus, longer foam half-lives or stability is one of the key factors determining the success of any foam-field application. The ability of surfactants to stabilize foam depends on the gas type. Many surfactants that form s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It is possible that the lower apparent viscosity in the low-foam-quality regime, which causes this curve shape, is due to the dissolution of some of the CO 2 into the injected water (thus reducing the foam quality and the total flow velocity at the same time), but corrections were already made for the solubility of the CO 2 during the calculation of the gas injection rate. Others have also seen this type of concave curve shape, both with CO 2 in sandstone ,,, and in limestone , and also in tests in capillary tubes. ,, It is known that gas diffusion through the bubble films is significantly higher for CO 2 than for N 2 , which would lead to more rapid foam coarsening. This coarsening, along with the lower pH produced by the CO 2 dissolution, explains the generally weaker foams observed with CO 2 .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…It is possible that the lower apparent viscosity in the low-foam-quality regime, which causes this curve shape, is due to the dissolution of some of the CO 2 into the injected water (thus reducing the foam quality and the total flow velocity at the same time), but corrections were already made for the solubility of the CO 2 during the calculation of the gas injection rate. Others have also seen this type of concave curve shape, both with CO 2 in sandstone ,,, and in limestone , and also in tests in capillary tubes. ,, It is known that gas diffusion through the bubble films is significantly higher for CO 2 than for N 2 , which would lead to more rapid foam coarsening. This coarsening, along with the lower pH produced by the CO 2 dissolution, explains the generally weaker foams observed with CO 2 .…”
Section: Resultsmentioning
confidence: 84%
“…Others have also seen this type of concave curve shape, both with CO 2 in sandstone ,,, and in limestone , and also in tests in capillary tubes. ,, It is known that gas diffusion through the bubble films is significantly higher for CO 2 than for N 2 , which would lead to more rapid foam coarsening. This coarsening, along with the lower pH produced by the CO 2 dissolution, explains the generally weaker foams observed with CO 2 . If this weakening effect becomes more significant at lower foam qualities, this would result in the concave curve shape.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Surfactants with strong adsorption have higher losses in the formation process. Zhou Jimin suggested that the static adsorption of the foaming agent should be at least 1mg/g or less [6]. In this paper, the adsorption of FM51 on the surface of quartz sand was measured.…”
Section: Fm51 Adsorption Performance Measurementmentioning
confidence: 95%
“…26,27 Zhou et al evaluated amphoteric surfactants to enhance the stability of CO 2 -foams at reservoir conditions. 29 Rossen et al addressed challenges associated with foam-assisted CO 2 storage where the surfactant is added to the aqueous phase. 28 To the best of our knowledge, this work represents the first laboratory assessment of CO 2 -soluble surfactants to improve CO 2 storage.…”
Section: Introductionmentioning
confidence: 99%